Edukasi Edukasi dan Pengembangan Inovasi Desa Wisata Berbasis Local Indegenous melalui Program Digitalisasi-Android di Kenagarian Simawang - Zulbahri; Welis, Wilda; Susanto, Nugroho; Zalindro, Ade; Supendra, Dedi; Firdaus, Kamal (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Simawang Village is located in Rambatan District, Tanah Datar Regency, West Sumatra Province. The area of ​​Simawang Village is 40.22 square kilometers or 31.14 percent of the area of ​​Rambatan District. Simawang has a population of 8,251 people, consisting of 4,014 men and 4,237 women and 1,968 households consisting of 8 jorong, namely: Ombilin, Padang Data, Darek, Baduih, Koto Gadang, Pincuran Gadang, Batu Limbak and Piliang Bendang. Simawang with its strategic location on the highway is one of the places that attracts tourists, due to the many destinations and natural tourist attractions, cultural arts and culinary delights that are very interesting in this village. The implementation of this PKM activity is basically aimed at improving and increasing the community's economy by increasing community insight and knowledge regarding management, administration, promotion, management, marketing, utilization of technology in the development of the tourism sector, cultural arts and culinary. The target of this PKM activity is to improve and develop the potential of natural tourism through sports tourism, ecotourism, local cultural arts and culinary specialties of the Simawang village. Community service activities or partnerships include; recruitment of participants, implementation of training activities, coaching, guidance and development of activities using the Participation Actions Learning System (PALS) method, real development by tourism managers through partner participation in training and coaching and evaluation of activities. This PKM program was initiated digitally-android with the aim of making the community more effective in promoting tourism, cultural arts and regional culinary specialties based on android in the Simawang village area, Rambatan sub-district, Tanah Datar district using mobile phones, laptops and other media.